The use of vacuum metal deposition for forensic casework in Canada. (29th July 2019) - Lam, Rolanda
ABSTRACT: Canada has seen a positive shift in the use of vacuum metal deposition as a fingermark detection method. This article examines the current state of this technique in Canada and offers recommendations and strategies to overcome challenges still present in an attempt to further advance the application of this extremely versatile technique.